Health Needs and Health Problems of Childbearing Women in Oyi Local Government area of Anambra State, Nigeria - Nwoye Catherine Ukamaka (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Maternal health remains a major public health concern in many parts of Nigeria, where access to quality healthcare services is often limited. In rural and semi-urban communities such as Oyi Local Government Area in Anambra State, childbearing women face numerous challenges that affect their health and that of their newborns. Objective: This study examines the health needs and challenges of childbearing women in Oyi, with a specific focus on maternal health as a key aspect of public health. Method: A mixed-method approach was adopted, involving surveys, interviews, and healthcare data analysis to explore the cultural, socioeconomic, and healthcare access factors influencing maternal health in the area. Result: Findings reveal critical health needs, including access to prenatal and postnatal care, nutritional support, and mental health services. Pregnancy-related complications and postpartum conditions are common, often worsened by inadequate healthcare access and financial limitations. Conclusion: Addressing these issues requires a comprehensive approach that involves community participation, supportive health policies, and improved healthcare provider training. Contribution: This study underscores the need to strengthen healthcare systems, expand maternal health education, and implement affordable, community-centered policies for sustainable improvements in maternal health in Oyi.